Native bluegill influence the foraging and aggressive behavior of invasive mosquitofish - Jennifer H. Clemmer; Jessica E. Rettig (PeerJ, 2019)
Two fish species that are common invaders of aquatic ecosystems world-wide are Gambusia affinis and G. holbrooki, commonly known as mosquitofish. In North America, introduced G. affinis are thought to have contributed to the population decline of several native fish species. Sunfish (family Centrarchidae) naturally occur across much of North American, thus mosquitofish and sunfish are likely to come into contact and interact more frequently as mosquitofish spread. However, the nature of this interaction is not well known. We used a lab experiment to explore whether and how the aggressive and foraging behaviors of G. affinis might be influenced by a representative and ubiquitous native centrarchid (Lepomis macrochirus; bluegill sunfish), a species with juveniles that inhabit littoral habitats also preferred by mosquitofish. The experiment partnered an individual male or female mosquitofish (focal fish) with a juvenile bluegill, or a same- or opposite-sex conspecific, filmed these one-to-one interactions, and quantified foraging and aggressive actions for the focal mosquitofish. We found that juvenile bluegill affect foraging in male mosquitofish, resulting in lower percent of handling attempts and handling time in which the male consumed a food item. The presence of juvenile bluegill also led to a reduction in the number of aggressive acts by mosquitofish compared to aggression levels when focal mosquitofish were with conspecifics. In nature, when mosquitofish encounter juvenile bluegill in littoral habitats, our results suggest that the foraging and aggressive behaviors of mosquitofish will be modified, especially for males. This mechanism may influence the rate or geographic extent of the spread of mosquitofish into North American waterbodies.